Field-scale spatial variability of physical properties of black soils of Purna Valley, India, using Geostatistical Approach - NAITAM, R. K.; KHARCHE, V. K.; KADU, P. R.; MOHRANA, P. C.; SHARMA, R. P. (Journal of Soil and Water Conservation, 2018)
The analysis of the spatial variability of soil properties is important for precision agriculture, land use planning and environmental modelling. Soil texture (sand, silt and clay) and soil hydraulic properties like available water capacity and hydraulic conductivity are most important soil physical properties that govern nearly all of the soil attributes. The objective of the study was to determine the degree of spatial variability of sand, silt, clay, bulk density, hydraulic conductivity and available water content at field capacity (FC), permanent wilting point (PWP) and available water capacity (AWC) of salt affected black soils of Purna valley. Data were analyzed both statistically and geostatistically to describe the spatial distribution of soil physical properties. Soil physical properties showed large variability with greatest variation was observed in hydraulic conductivity (54%). Spherical and gausian models were fit well for the soil physical properties. The nugget/sill ratio indicates that hydraulic conductivity, clay, silt content and soil water content at field capacity were strongly spatially dependent and all other soil physical properties were moderate spatially dependent. Cross validation of the kriged map shows that prediction of the soil physical properties using semivariogram parameters is better than assuming mean of observed value for any unsampled location. The spatial distribution of hydraulic conductivity and bulk density followed the distribution pattern of clay and exchangeable sodium content. These maps will help to the planners in site-specific management/precision farming by application of the correct measures for improving the physical properties of these degraded shrink-swell soils through application of gypsum, FYM and green manuring through variable rate techniques.